Genotype and cytokinin effects on soybean yield and biological nitrogen fixation across soil temperatures - Kempster, Robert (2020)
High nitrogen (N) supply is required for high‐yielding soybean, but low soil temperatures in either early production systems or cool environments delay nodulation and limit biological nitrogen fixation (BNF). Because cytokinins are key signalling hormones in mediating nodule formation and our initial controlled environment experiment indicated that seed cytokinin treatment increased early BNF and total nodule area, it was used in field trials. Cytokinin was applied (seed or foliar) to two commercial soybean genotypes (DM50I17 and DM40R16) in field trials with early (September and early November) and conventional (late November) sowing dates in Argentina. In the field, DMR50I7 achieved consistent yields across sowing dates because increased BNF compensated for limited soil N uptake in early sowing dates, also leading to 25% higher nitrogen use efficiency (NUE). Surprisingly, soil N uptake was more cold‐sensitive than BNF with greater and prolonged N fixation in early sowing, perhaps through delayed nodulation, leading to improved N harvest index. Cytokinin seed treatment increased BNF (26%) in DM40R16 especially in early sowing dates. Although cytokinin improved cold tolerance of BNF, this was not explained by altered nodulation and did not increase yield. Here we show genetic differences in N supply in commercial soybean genotypes and the importance of BNF to maintain yield in early sown soybean.